Research and Simulation of the Inrush Current for the CRH3 EMUs Traction Transformer - 姜东杰; 王师昂 (机车电传动)
Based on the analysis of the mechanism and properties of the traction transformer inrush current , and specially on the characteristic of the CRH3 EMUs traction transformer, the simulation was carried out by the the MATLAB software, the result of the simulation in accordance with the actually technical parameter, which validated the model. Meanwhile analyzed the inrush current with Fourier method, and the result of the analysis proves that the method of EMUs traction transformer differential protection by estimation secondary harmonic proportion is possible.